An enabling environment for female leadership in Finnish comprehensive school - Zeh, Sang (2016)
Though women account for over one-half of the potential talent known throughout the world, as a group they have been subordinated and their economic, social and environmental contributions go in large part unrecognized. This is due to gender socialization which is based on the socially-constructed and historically- developed roles of men and women; putting men as actors whilst women are at the recipient end. However, the scenario in Finland shows a slightly high level of equality as there are many female leaders in Finland. Global Gender Gap Report 2013 p. 9. Thus this study aimed to explore the factors that have created an enabling environment for female leadership in Finnish comprehensive schools. This study used qualitative phenomenological methodology to invoke the perspectives of each of the participants’ experiences. Purposive interviews were used to collect data from five female principals in different comprehensive schools in Jyaskyla. Thematic analysis of data led to the discovery of four principal themes which altogether answered all the three research questions and addressed the subject matter. Data revealed that the overall structural elements, that is the institutional aspect, culture, norms and values in Finland build gender equitable environment which goes a long way to promote female leadership in Finland. This holds true that gender equality is more entrenched in Finland. From the respondent’s experiences, gender as it self, is not important. What is important is the personality. However, these women still face challenges as leaders next as female leaders.